Quality of Marketing Research: A Citation Analysis - Mohammadreza Haji-Basri; Ahmad Abareshi (STIE Malangkucecwara, 2015)
This paper examines the extant research in marketing discipline by conducting a bibliometric study of the articles published in three leading marketing journals of over the period between 2000 and 2010. The focus of this paper is two fold: a). using an approach of combining content analysis and citation analysis on a sample of 1534 articles this paper investigates the impact of research method and research theme on the quality of the articles published in three marketing journals, and b). using a descriptive analysis this paper examines the current and future direction of the marketing practice. Regression analysis reveals that empirical research with field data along with consumer behaviour are more likely to be cited within and outside of marketing discipline. The results also reveal the research trends of the marketing research. The findings of this study can be used as the direction of marketing practice by researchers, editors, and reviewers.